2014
DOI: 10.1007/s11748-014-0489-4
|View full text |Cite
|
Sign up to set email alerts
|

A case of simultaneous bilateral spontaneous pneumothorax after the Nuss procedure

Abstract: We present a case of simultaneous bilateral spontaneous pneumothorax caused by a pleuro-pleural communication formed from Nuss procedure for pectus excavatum. A 17-year-old man with a history of Nuss operation complained chest pain and dyspnea. A chest roentgenogram demonstrated a tiny bilateral pneumothorax and two metallic bars inserted at the Nuss procedure. Computed tomography revealed furthermore a bulla in the apex of the left lung. The bilateral pneumothorax critically deteriorated after 4 days from ons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The surgical outcomes of PE correction have been progressively improving because of advances in minimally invasive surgical techniques (5). However, the chest wall corrected by the Nuss procedure becomes more vulnerable to pneumothorax, and there are several reports of lifethreatening cases of bilateral PSP in a buffalo chest following the Nuss procedure for PE (16)(17)(18). The potential risk involves the development of bilateral pneumothorax in a buffalo chest due to bilateral thoracic cavity communication following the Nuss bar insertion, which can have catastrophic consequences if not promptly and appropriately managed surgically.…”
Section: Discussionmentioning
confidence: 99%
“…The surgical outcomes of PE correction have been progressively improving because of advances in minimally invasive surgical techniques (5). However, the chest wall corrected by the Nuss procedure becomes more vulnerable to pneumothorax, and there are several reports of lifethreatening cases of bilateral PSP in a buffalo chest following the Nuss procedure for PE (16)(17)(18). The potential risk involves the development of bilateral pneumothorax in a buffalo chest due to bilateral thoracic cavity communication following the Nuss bar insertion, which can have catastrophic consequences if not promptly and appropriately managed surgically.…”
Section: Discussionmentioning
confidence: 99%
“…Abrasion near the Nuss bar is not recommended because excess adhesion may compromise the subsequent Nuss bar removal procedure. There were two reported cases developed bilateral pneumothorax after Nuss correction: Sakamoto reported that a 14-year-old boy developed dyspnea 2 months after correction surgery [17] and Matsuoka reported that one 17-year-old man had bilateral PSP 16 months after the Nuss operation [18]. The possible risk is iatrogenic buffalo chest caused by communication of the bilateral thoracic cavity after Nuss bar insertion.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with severe pectus excavatum, this defect cannot be completely healed in the short term. Patients with pectus excavatum comorbid by pulmonary bulla and ruptures during this period are prone to serious bilateral pneumothorax, which is difficult to cure by drainage alone; a bullectomy is needed (19,20) All the patients in this group were given a chest CT examination before an operation. Two cases were found to have comorbid pulmonary bulla; both patients were given pulmonary bulla incisions and pectus excavatum surgeries in the same period after we fully communicated with them and obtained their consent.…”
Section: Discussionmentioning
confidence: 99%